Daily Mobility in Berlin: On ’Inner Unity’ and the Explanation of Travel Behaviour - Scheiner, Joachim (European Journal of Transport and Infrastructure Research, 2005)
The article deals with the process of integration of East and West Berlin by means of the population's everyday mobility. Analysing activity spaces in four small-scale study areas on both sides of the former Berlin wall, there is evidence for significant differences between adjacent areas on both sides of the former wall as well as between different groups within an area. The interviewees' place of origin plays an important role. The question is, how – on the one hand – groups of persons might be characterised who tend to integrate the respective other half of the city more strongly into their everyday life ('border crossers') or – on the other hand – people still tend to concentrate on their respective half of the city a decade after the fall of the wall ('half-urbanites'). On the basis of spatial behaviour and the attitude towards the city's other half, four groups are differentiated. They are examined by a discriminant analysis as well as on the basis of semi-structured interviews with regard to dominating patterns of interpreting the German unification and their own personal identity. These patterns provide a considerable contribution for a better understanding of group-specific differences in the choice of mobility behaviour. From these results, consequences are drawn for the explanation of travel behaviour and for the theory and methodology of travel behaviour research. The hypothesis is developed that spatial action may not fully be explained by restrictive factors (infrastructure, distribution of opportunities, socio-demographic factors etc.). Additional factors which are empirically much more difficult to handle, such as attitudes, lifestyles, biographical experiences and long-term spatial orientations, are playing a role. The modelling of travel behaviour is theoretically incomplete by neglecting individual reasons of action. Any prediction of the future transport development might at least partly suffer from this weakness.